Adopting Partnership in Learning, Teaching, and Assessment as a Strategy to Foster the EFL Learning Process: The Case of Third Year English Language Learners, Mohammed Boudiaf University, M’sila - Imane ZIAM, Malika BELHADJ (My University, 2018)
iv ABSTRACT The present study investigates the effectiveness of partnership in learning, teaching, and assessment in improving the English language learning process of English department students at M'sila university. It also attempts to shed light on the importance of establishing a relaxed and friendly environment in reducing psychological problems and increasing the learners’ motivation. The study aims to raise the awareness of teachers and students about the importance of partnership in learning, teaching, and assessment in facilitating the learning process. This investigation was conducted among the third year students of English department of M'sila university. It was based on the use of the descriptive research where data were collected both qualitatively through classroom observation and quantitatively through questionnaire. The findings revealed that treating students as partners increases their sense of responsibility and their level of engagement; and hence, promoting their learning. It also revealed that teachers and students awareness of the importance of such relationship provides them with better learning and teaching experiences. This research tackled descriptively one area of partnership, so further research suggests the use of experimental research to prove the applicability of this strategy and widen it to other areas of partnership which are subject-based research and inquiry, scholarship of teaching and learning, curriculum design and pedagogical consultancy.
Keywords: Keywords: Partnership, staff-student partnership, EFL learning process, teaching experience, learning experience, learning environment.